PROFIL KOMPETENSI PEDAGOGICAL CONTENT KNOWLEDGE (PCK) GURU IPA SMP DI KABUPATEN SIAK - Agustin, Putri Andini; Natalina, Mariani; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this study was to describe Science teachers’ Pedagogical Content Knowledge (PCK) at Public Junior High School in Siak Regency. This study held on November 2017 until March 2018. The sample of this study was 53 science teachers at Public Junior High School in Siak Regency that selected by purposive sampling. This study conducted with question test of Pedagogical Content Knowledge develop by Tari Rezky Ayunda (2017), closed-ended and open-ended questionnaire. The question test of Pedagogical Content Knowledge consist 96 items. The questionnaire consists 40 items of closed-ended and 5 items of closed-ended, which is it divided to 3 subdomains. The subdomains are Pedagogical Knowledge (PK), Content Knowledge (CK), and Pedagogical Content Knowledge (PCK). The questionnaire items is valid and reliable. Descriptive study was implemented in this study. The result showed that science teachers’ PCK at Public Junior High School in Siak Regency was not good enough (M=52,02%), PK was very not good (M=43,93%), CK was not good (M=57,48%), and PCK was not good (M=54,66%). That result indicated that science teacher at Public Junior High School in Siak Regency could not implement their pedagogical content knowledge in science learning.Key Words: Pedagogical Content Knowledge, Junior High School, Science Teacher